IMPLEMENTASI PROJECT BASED LEARNING DALAM MENINGKATKAN MOTIVASI BELAJAR PENDIDIKAN AGAMA ISLAM - Nur Esa; Abdul Halik; Musyarif (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the level of students' learning motivation in Islamic Religious Education before and after the implementation of project-based learning. Additionally, it seeks to describe the implementation of project-based learning in Islamic Religious Education and assess whether its application is effective in improving students' learning motivation. The primary research question is whether the implementation of project-based learning effectively enhances the learning motivation of Islamic Religious Education students at SDN 160 Salokalama, Enrekang Regency. This research employs an experimental approach, specifically a pre-experimental design with a one-group pretest-posttest design. The study population consists of 97 students, with a sample of 13 students selected using purposive sampling. Data collection techniques include tests, questionnaires, and documentation. The research instruments comprise pretests, posttests, and questionnaires, while data analysis utilizes descriptive statistical analysis and inferential statistical analysis. The findings reveal: (1) The students' learning motivation level before the implementation of project-based learning was categorized as low, with an average pretest score of 30.00. After implementation, motivation increased significantly, with an average posttest score of 84.62. (2) The implementation of project-based learning was effectively applied in the fifth grade of SDN 160 Salokalama, Enrekang Regency. Students actively participated in learning through creative and relevant projects, such as mind mapping, aligned with Islamic Religious Education material. (3) Project based learning proved effective in enhancing students' motivation in Islamic Religious Education, as evidenced by the N-Gain score test, which showed a 0.7654 (76.5%) improvement in learning motivation—classified as effective.